2016
DOI: 10.1021/acscatal.6b01036
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Water Splitting Catalysis with a High FF Triple Junction Polymer Cell

Abstract: We report a photovoltaics-electrochemical (PV-EC) assembly based on a compact and easily processable triple homo-junction polymer cell with high fill factor (76%), optimized conversion efficiencies up to 8.7 % and enough potential for the energetically demanding water splitting reaction (Voc = 2.1 V). A platinum-free cathode made of abundant materials is coupled to a ruthenium oxide on glassy carbon anode (GC-RuO 2 ) to perform the reaction at optimum potential (ΔE = 1.70-1.78 V, overpotential = 470-550 mV). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
(97 reference statements)
0
37
0
Order By: Relevance
“…As a result, after a few catalytic cycles, the only Ru species left at the electrode surface are RuO 2 NPs. With a TOF i of 300 s −1 at Γ =1.0 pmol cm −2 , this system outperforms the state‐of‐the‐art systems prepared ex situ by several orders of magnitude (see TOF data in Tables and ), and it has been incorporated into a photovoltaic electrolyzer cell (PV‐EC), together with an earth‐abundant cathode and a triple‐junction polymer cell, to achieve solar to hydrogen conversion efficiencies of around 6 % . The reasons for the strikingly fast kinetics of this in situ generated RuO 2 electrocatalyst still remain unclear.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…As a result, after a few catalytic cycles, the only Ru species left at the electrode surface are RuO 2 NPs. With a TOF i of 300 s −1 at Γ =1.0 pmol cm −2 , this system outperforms the state‐of‐the‐art systems prepared ex situ by several orders of magnitude (see TOF data in Tables and ), and it has been incorporated into a photovoltaic electrolyzer cell (PV‐EC), together with an earth‐abundant cathode and a triple‐junction polymer cell, to achieve solar to hydrogen conversion efficiencies of around 6 % . The reasons for the strikingly fast kinetics of this in situ generated RuO 2 electrocatalyst still remain unclear.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…With respect to the tandem cell, the efficiency of the triple‐junction cells was lower (PCE of 8.35% for the tandem and PCE of 7.42% for the triple), likely due to the fact that the tandem already afforded a nearly complete absorption of light. Two additional examples about the use of triple‐junction polymer solar cells for water splitting will be discussed in Section . Di Carlo Rasi et al reported three triple‐junction solar cells fabricated using the same PEDOT:PSS/zinc oxide ICL, also discussed in Section .…”
Section: Triple‐ and Quadruple‐junction Solar Cellsmentioning
confidence: 99%
“…The cell thus affords η STH of 6.6% when assuming 100% Faradaic efficiency. In the same year, Elias et al presented a homo‐triple junction for water splitting, i.e., using the same absorber in all the three subcells, PTB7:PC 70 BM . The structure of this device was inverted, with the successful MoO 3 /Ag/PFN stack as ICL.…”
Section: Use Of Multijunction Polymer Solar Cellsmentioning
confidence: 99%
“…There are few examples of triple-junction organic solar cells. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The gain in efficiency achieved by these triple-junction devices was not always accompanied by a critical analysis of the measured performance. In a recent publication, Timmreck et al methodically analyzed the literature on tandem organic solar cells, shedding light on the fact that the vast majority of the publications on organic tandem cells lacked a proper characterization.…”
mentioning
confidence: 99%
“…At present, the characterization of organic triple-junctions is often limited to measuring the J−V characteristics under simulated solar radiation and determining the external quantum efficiency (EQE) using different light sources to optically bias the subcells. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Nevertheless, organic materials commonly employed for solar cells feature peculiar characteristics that necessitate special attention for their EQE measurement. [42][43][44] An accurate analysis of the effect of bias light and bias voltage on the EQE of triple-junction organic solar cells is necessary.…”
mentioning
confidence: 99%